Land Restoration in Latin America and the Caribbean: An Overview of Recent, Ongoing and Planned Restoration Initiatives and Their Potential for Climate Change Mitigation - Romijn, Erika; Coppus, Ruben; Sy, Veronique de; Herold, Martin; Román Cuesta, Rosa María; Verchot, Louis V. (MDPI, 2019)
Land degradation is a globally recognized problem and restoration of degraded land is currently high on the international agenda. Forest landscape restoration and other restorative ecosystem management activities are important measures that contribute towards reaching the objectives of the Bonn Challenge, which aims to restore 350 million hectares by 2030. In this context, many restoration projects are being planned and implemented in Latin America and the Caribbean (LAC). We present an overview of the location, goals and activities, and an estimated climate change mitigation potential of 154 recent, ongoing and planned restoration projects in LAC. Our analysis suggests that most projects are located in the humid tropics and less attention is paid to drylands. Increasing vegetation cover, biodiversity recovery and recovery of ecological processes are the most common goals. Restorative activities to fulfil these goals were diverse and were related to the type and source of funding that projects receive. For example, projects implemented through the Forest Investment Program (FIP) and the Global Environment Facility (GEF) generally rely on natural or assisted regeneration over large areas (>20,000 ha), whereas Clean Development Mechanism (CDM) projects establish forest plantations, often including exotic monocultures, in smaller project areas (<5000 ha). Projects that are specifically implemented within the scope of Initiative 20 × 20 and other local initiatives that target the local environmental problems, are more varied and rely on a wider portfolio of restorative activities, such as erosion control, exclusion of grazing and mixed plantations. These projects are usually implemented in smaller project areas (<5000 ha). All projects had the potential to contribute to climate change mitigation by storing additional forest aboveground biomass through natural regeneration, assisted regeneration or establishing a plantation. Further analysis of the implemented activities is an important next step to investigate their effectiveness in terms of goals achieved under Initiative 20 × 20 and the Bonn Challenge. This would provide information for future restoration projects and upscaling of restorative activities in a wider area.